2017
DOI: 10.1002/acm2.12151
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: TROG 15.01 SPARK trial multi‐institutional imaging dose measurement

Abstract: PurposeThe Trans‐Tasman Radiation Oncology Group (TROG) 15.01 Stereotactic Prostate Adaptive Radiotherapy utilizing Kilovoltage intrafraction monitoring (SPARK) trial is a multicenter trial using Kilovoltage Intrafraction Monitoring (KIM) to monitor prostate position during the delivery of prostate radiation therapy. KIM increases the accuracy of prostate radiation therapy treatments and allows for hypofractionation. However, an additional imaging dose is delivered to the patient. A standardized procedure to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Table 4 shows a comparison of results from previous studies on pelvis and thorax imaging dose using different real-time tumor monitoring technologies. The first two studies (Juneja et al 2016, Legge et al 2017 have reported the imaging dose for real-time tumor monitoring with Kilovoltage Intrafraction Monitoring (KIM) technology for lung IGRT and prostate IGRT respectively. They measured surface dose and absorbed dose to PTV following the Institution of Physics and Engineering in Medicine and Biology (IPEMB) protocol (IPEMB 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 shows a comparison of results from previous studies on pelvis and thorax imaging dose using different real-time tumor monitoring technologies. The first two studies (Juneja et al 2016, Legge et al 2017 have reported the imaging dose for real-time tumor monitoring with Kilovoltage Intrafraction Monitoring (KIM) technology for lung IGRT and prostate IGRT respectively. They measured surface dose and absorbed dose to PTV following the Institution of Physics and Engineering in Medicine and Biology (IPEMB) protocol (IPEMB 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The mean of estimated imaging doses for ipsilateral and contralateral lung, heart and spinal cord were 122 mGy, 56 mGy, 80 mGy and 65 mGy, respectively. Legge et al (2017) also measured the imaging dose in prostate patient using the same system. The estimated imaging doses to the prostate for all five treatment fractions were 39.9 ± 2.6 mGy for 1 Hz imaging, 199.7 ± 13.2 mGy for 5 Hz imaging and 439.3 ± 29 mGy for 11 Hz imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible perovskite-based X-ray detectors have been less explored but, in the last years, the number of reports on their feasibility is rapidly growing. [35][36][37] The possibility of conforming ionizing radiation detectors and dosimeters onto a nonflat object is one of the primary desired features needed, for example, when detectors have to be integrated inside specific probes during radiation therapy, [38] or in easy-wearable objects (e.g., bracelets and belt) and for potential vignetting limitation. Recently, Zhao et al [39] proposed a highly sensitive and flexible direct X-ray detector based on a porous nylon membrane with metal halide perovskite loaded by the infiltration method.…”
Section: Introductionmentioning
confidence: 99%